Efektifitas Penggunaan Streptokinase Pada Pasien Infark Miokard Akut: A Literature Review - Septin Nabila Fakhira Driela Putri; Wachidah Yuniartika (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Acute coronary syndrome (ACS) is one of the largest cardiovascular diseases in the world, resulting in high hospitalization and mortality. The importance of early intervention and optimal treatment strategies with an emphasis on diagnosis is necessary to reduce mortality from heart disease, especially myocardial infarction. One such strategy is the timely reperfusion of infarcted coronary arteries using fibrinolysis in which streptokinase therapy is used. The aim of this study is to determine the efficacy of streptokinase use in patients with acute myocardial infarction. The search methodology was a literature search using database sources such as Cochrane, Crossref, Google Scholar, PubMed and Scopus, and included seven articles reviewed with publication coverage from January 1st 2015 to September 19th 2022. Results of a literature review show that administration of streptokinase thrombolysis is effective in the initial treatment of patients with acute myocardial infarction. This literature review concludes that fibrinolytic therapy with streptokinase class drugs is effective in patients with acute myocardial infarction due to its high efficacy, high availability, low cost, and low incidence of bleeding complications. It means that it can be used for nonetheless, if patients require rigorous follow-up while on streptokinase therapy associated with complications including death, patient follow-up or observation for long-term measures is warranted.